Examining the Ethical Use of Artificial Intelligence by Journalists. A Case Study of the Standard, UCU - Aldrine Adson Aine (Uganda Christian University, 2024)
This study examines the ethical use of Artificial Intelligence (AI) by journalists at The Standard, the official student newspaper of Uganda Christian University (UCU). The research aims to investigate the current practices and attitudes of journalists regarding AI use in news production, analyze the ethical implications of AI applications in journalism, and explore the need for ethical guidelines to ensure responsible AI use by journalists. The study employs a qualitative case study design, conducting in-depth interviews with six journalists from The Standard. The findings reveal that journalists are using various AI tools, primarily for research and data analysis, but they express concerns about the potential impact of AI on accuracy, reliability, transparency, and accountability in journalism. The journalists emphasize the need for human oversight, fact-checking, and diverse perspectives in the deployment of AI, as well as the development of ethical guidelines and regulations to govern the responsible use of AI in the newsroom. The study's findings contribute to the limited existing research on the ethical use of AI in journalism, particularly within the Ugandan context. The insights gained from this research can inform strategies for promoting responsible AI use, ensuring accountability and transparency in the media, and developing targeted training programs for journalists on ethical AI practices. The study's implications extend beyond the journalism industry, providing valuable insights for the broader discussion on AI ethics and its responsible integration across various sectors.
Undergraduate research